A1.45 Hyperglycosylation of ACPA-IGG variable domains modulates reactivity to citrullinated antigens. (31st January 2014) - Rombouts, Y; Willemze, A; van Beers, J J B C; Shi, J; Kerkman, P F; Janssen, G M C; van Veelen, P A; Zaldumbide, A; Hoeben, R C; Pruijn, G J; Deelder, A M; Wolbink, G; et al.
Abstract : Background and Objectives: Autoantibodies specific for citrullinated antigens are highly relevant diagnostic and prognostic biomarkers in rheumatoid arthritis and have been considered to be involved in disease pathogenesis. Previous studies have indicated that the ACPA-specific immune response differs from conventional B cell responses by generating polyclonal, cross-reactive antibodies of mostly low-avidity. In addition, ACPA were found to carry aberrant glycosylation patterns at the IgG-Fc tail. The present study was undertaken to further characterise the molecular make-up of ACPA and its potential functional consequences in the context of RA. Materials and Methods: Serum components of RA patients were fractionated by size exclusion chromatography and analysed for the presence of ACPA-IgG by ELISA. In addition, ACPA-IgG and non-citrulline-specific IgG were affinity purified from RA patient serum and synovial fluid and analysed by gel electrophoresis. Electrophoresis bands were excised and subsequently analysed by HPLC and mass-spectrometry. Recombinant monoclonal ACPA with variations in ACPA molecular structure were used to study binding affinity by surface plasmon resonance. Results: We discovered that ACPA-IgG from RA patients have a higher apparent molecular weight as compared to other IgG molecules including antibodies against recall antigens and other autoantibodies. This higher molecular weight was explained by the overrepresentation of N-linked glycans in the variable domain (Fab region) of ACPA-IgG. Detailed structural analysis of these glycans demonstrated that ACPA-IgG linked Fab glycans are complex-type biantennary N-glycans that differ from the conventional Fc-linked N-glycans by a high degree of sialylation, galactosylation, and fucosylation together with the presence of bisecting N-acetylglucosamine. Using recombinant ACPA-IgG monoclonal antibodies with and without Fab-glycans, we found that Fab-glycans modulate binding affinity of ACPA-IgG for citrullinated antigens. Finally, lectin-immunoblotting showed that ACPA Fab-glycans can bind to sialic acid-binding immunoglobulin-type lectins. Conclusions: This study describes an unusual and novel molecular feature of the citrulline-specific immune response in RA. ACPA-IgG, in contrast to non-citrulline-specific IgG, are highly glycosylated in the variable region, which modulates recognition of citrullinated antigens. Moreover, ACPA-IgG linked Fab glycans can be the target of specific lectins, suggesting additional functional features potentially involved in ACPA-mediated pathogenetic effects. This finding points to aberrations in the development of ACPA-specific B cells and further elucidates our understanding of basic disease mechanisms in RA.